2021
DOI: 10.21608/svuijas.2021.99388.1146
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of some hematological parameters of broiler and indigenous breeds of poultry

Abstract: The investigational trials were conducted on day-old, total ninety chicks of broilers and indigenous (IND) poultry breeds in controlled conditions to analyze some hematological parameters. Water and basal diet were provided ad libitum. The experiment was carried out for 20 weeks. A total of 40 blood samples 20 for each breed were collected in a randomized manner through a brachial cut at the end of the trial. Hematological parameters, i.e., RBCs (10 6 /μl), WBCs (10 3 /μL), Lymphocytes (10 3 /μL), Monocytes (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
1
4
0
2
Order By: Relevance
“…addition, average erythrocyte size, haemoglobin amount per blood cell, and the amount of haemoglobin relative to the size of the cell per red blood cells were studied. Although, the MCV, MCH and MCHC values reported in this work were lower than broiler normal means values of 174 fL for MCV, 61pg/cell for MCH and 33 g/dl for MCHC reported by Merck (2012) for broilers, it is worthy of note that these values reported in this study are in line with the MCV, MCH and MCHC values reported for broilers by Onunkwo et al (2018), Odunitan-Waya et al (2018, Ifelayo et al (2020) and Muneer et al (2021), and within the normal ranges of 90-140fL (MCV), 33-47 pg/cell (MCH) and 26-35 g/dl (MCHC) reported for broilers by Bounous and Stedman (2000). Hence, the ability of the extracts to maintain the MCV, MCH, MCHC levels of colibacillosis infected broilers indicates that they may possess phytobiotic properties against the E. coli as well as the tendency to restore blood quality.…”
Section: Insupporting
confidence: 81%
“…addition, average erythrocyte size, haemoglobin amount per blood cell, and the amount of haemoglobin relative to the size of the cell per red blood cells were studied. Although, the MCV, MCH and MCHC values reported in this work were lower than broiler normal means values of 174 fL for MCV, 61pg/cell for MCH and 33 g/dl for MCHC reported by Merck (2012) for broilers, it is worthy of note that these values reported in this study are in line with the MCV, MCH and MCHC values reported for broilers by Onunkwo et al (2018), Odunitan-Waya et al (2018, Ifelayo et al (2020) and Muneer et al (2021), and within the normal ranges of 90-140fL (MCV), 33-47 pg/cell (MCH) and 26-35 g/dl (MCHC) reported for broilers by Bounous and Stedman (2000). Hence, the ability of the extracts to maintain the MCV, MCH, MCHC levels of colibacillosis infected broilers indicates that they may possess phytobiotic properties against the E. coli as well as the tendency to restore blood quality.…”
Section: Insupporting
confidence: 81%
“…Consequently, Guluwa et al (2017) reported that haemoglobin concentration within the normal range for healthy chicken indicates improved oxygen carrying capacity. Muneer et al (2021) reported that packed cell volume, HB and mean corpuscular heamoglobin are major indices for evaluating circulatory erythrocytes and are significant in the diagnosis of anemia and also serve as useful indices for bone marrow capacity to produce red blood cells like in human being. Furthermore, the white blood cells increased with increased inclusion levels of LMSM.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), and mean corpuscular hemoglobin concentration (MCHC), these were also calculated using the following formulae, according to Muneer et al (2021).…”
Section: Blood Indicesmentioning
confidence: 99%